Changes in the blood platelets of alcoholics during alcohol withdrawal. Issue 3 (March 1983) - Fink, R; Hutton, R A
Abstract : The effects of alcohol withdrawal on platelet count and platelet function was studied sequentially in a group of alcoholics. Baseline values for platelet count, platelet adenine nucleotides and plasma beta-thromboglobulin (beta TG) level were within the normal range but platelet aggregability (especially with ADP and adrenaline) and circulating platelet aggregates were decreased for the group as a whole. After alcohol withdrawal there was a pronounced increase in all parameters measured which reached statistical significance in many cases and persisted for two to four weeks. The potential implications and possible mechanisms for these changes are discussed.